A Systematic Review on Nanomedicine - Y. Nawaz, I. Nazar, H. Ahmad, M. S. Khan, L. Hakeem, A. Saddiqa, M. K. Ullah, H. R. Shafiaq. K. Iqbal, M. Waijad, B. Saeed (Pakistan Journal of Medical & Health Sciences, 2022)
Nanomedicine is used to cure cancer of many tissues such as ovarian cancer and multiple myeloma. With the help of nanotechnology, the probability of failure or rejection of a transplant, an organ is reduced. Nanomedicine is one of the latest and better fields which is used for the treatment of tumors. Some of the methods used to produce nanoparticles are discussed here. Many nanoparticles are used for the benefit of humans. The solvent is subsequently dispersed in a surfactant's aqueous media, resulting in the formation of a film in an instant colloidal suspension called solvent displacement. This method can be used to achieve a pharmacological payload. Supersaturation and precipitation are required for the assembly and stability of drug nanoparticles. Shear and cavitation forces are also used to produce nanoparticles. The milling media is generating shear forces on impact, resulting in nanoparticles, the principle of size reduction. Extrusion is also used to generate nanoparticles. Hydrophobic drugs are converted directly into nanoparticles. The capacity to build nanocores with a wide range of functionalities is another key advantage of the HAylation process (a method to make nanoparticles). Determine medication, metabolism and hepatotoxicity in these models in nanomedicine have the potential to have a significant influence in the field. Red blood cells (RBCs), for example, are sensitive to substantial external flow pressures, and their inherent formability can be used as a biomarker to identify a range of RBC diseases. It is concluded that different nanoparticles are made to treat different kinds of diseases and to make different therapies for cancer etc. Now a day’s nanotechnology is the method that uses nanoparticles to cure diseases and provide a significant treatment approach to humans.